Provider Payment Mechanisms to Health Centers, Thailand, 2006 - Pokpermdee, Pongsadhorn; Hausup, Janthima; Phuknuan, Prisana (Journal of Health Science of Thailand, 2018)
Health center is the most adjacent health care unit in the community. The appropriate provider payment to health centers will facilitate efficiency, quality, and access to care of patients. Provider payment to health centers therefore plays important roles in the outcomes of health care system. The objectives of this study were to understand the actual situation of the provider payment to health centers and to use this information to improve the provider payment method to health centers in Thailand. This study sent questionnaire to health insurance division of all provincial health offices and then used the telephone calls to clarify the terms and questions. The survey results indicated that there were several provider payment methods, types of budget and different amounts of budget allocated to health centers. This included the differences of size, indicators to differentiate the size of health centers, rate and method of reimbursement of by-passed patients to other health centers. In addition, the provincial health office still played an essential part in allocating resources to health centers meanwhile the role of CUP management decreased. This direction was not conducive to the direction used by the National Health Security Office – NHSO, which allocated budget directly to CUP. The recommendations to improve provider payment method of health centers are to find the appropriate method to differentiate size of health centers, explore amount of administration budget, and find the appropriate provider payment method of all budget items (outpatient, drug and material, prevention and promotion, bonus and capital investment budgets for health centers).